Powder Metallurgy Produced Aligned Long Tungsten Fiber Reinforced Tungsten Composites - Yiran Mao; Jan W. Coenen; Chao Liu; Alexis Terra; Xiaoyue Tan; Johann Riesch; Till Höschen; Yucheng Wu; Christoph Broeckmann; Christian Linsmeier (Journal of Nuclear Engineering, 2022)
For the future fusion reactor, tungsten is the main candidate material as the plasma-facing material. However, considering the high thermal stress during operation, the intrinsic brittleness of tungsten is one of the issues. To overcome the brittleness, tungsten fiber reinforces tungsten composites (Wf/W) developed using extrinsic toughening mechanisms. The powder metallurgy process and chemical vapor deposition process are the two production routes for preparing Wf/W. For the powder metallurgy route, due to technical limitations, previous studies focused on short random distributed fiber-reinforced composites. However, for short random fiber composites, the strength and reinforcement effect are considerably limited compared to aligned continuous fiber composites. In this work, aligned long tungsten fiber reinforced tungsten composites have been first time realized based on powder metallurgy processes, by alternately placing tungsten weaves and tungsten powder layers. The produced Wf/W shows significantly improved mechanical properties compared to pure W and conventional short fiber Wf/W.